Ghost world - Clowes, Daniel (Fantagraphics Books, 2008)
One of the best-selling and critically-acclaimed graphic novels of all-time telling the story of two supremely ironic, above-it-all teenagers facing the thrilling uncertainty of life after high school. As they attempt to carry their life-long friendship into a new era, the careful dynamics of their inseparable bond are jolted, and what seemed like a future of endless possibilities looks more like an encroaching reality of strip malls, low-paying service jobs and fading memories.